Formulation and Evaluation of meclofenamate fast dissolving tablet. - R, Hemraj; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2022)
The study of this work was to use a swellable polymer chosen among superdisintegrants, for improving the dissolution rate of a sparingly soluble drug, loaded on its surface. Meclofenamate, which has very low water solubility, was chosen as a model drug, while cross linked sodium carboxymethyl cellulose (Ac-Di-Sol) was chosen as the swellable polymer. The Drug Polymer systems were prepared using direct compression method.The results of the dissolution tests showed that the dissolution rate of Meclofenamate from the systems prepared increase, particularly in the case of the preparation composed of Ac-Di-Sol plus surfactant agents. Attempts were made to increase the rate of drug release (disintegration) to enhance the in vitro dissolution of the poorly soluble drug by using extra, intra and partly intra and extra granular method of addition of sodium starch glycolate as superdisintegrants and to develop a stable immediate release formulation by direct compression method.